Efecto de cuatro niveles (5, 10, 15 y 20%) de harina de papa (solanum tuberosum) en la alimentación de pollos de engorde en la fase de crecimiento y acabado en el CEASA. - Bedoya Umaquinga, Diana Mercedes (2020)
This research work was carried out in the experimental poultry project of the Veterinary Medicine, Faculty of Agricultural Sciences and Natural Resources, of the Technical University of Cotopaxi, located in the province of Cotopaxi, Latacunga city, Eloy Alfaro parish, Salache neighborhood low with geographical coordinates 0 ° 59'45.7 "S of latitude, 78 ° 37'30.9" W of longitude and 2777.011 meters above sea level, for this investigation we used 100 chickens of the Ross 308 line of a day of age and continued until on the 49th day of age, to evaluate the effect of four levels (5, 10, 15 and 20%) of potato flour (Solanum tuberosum) in the feeding of broilers in the growth and finishing phase in CEASA . The birds were assigned to 5 dietary treatments; T0- (control treatment - Base diet), T1 - (Base Diet + 5% addition of Potato Flour), T2 - (Base Diet + 10% addition of Potato Flour), T3 - (Base Diet +15% Potato Flour addition) and T4 - (Base Diet + 20% Potato Flour addition). A completely random design (DCA) is applied with five repetitions for each treatment. The experimental units were homogeneous (CV: 6.71%), considering different sources of variability. The analysis of variance was carried out, with the Duncan significance tests at 5%, to differentiate between treatments. The economic analysis was performed by calculating the benefit/cost ratio (RBC). The best results were obtained in the treatments that were provided with the food diet consisting of 15% inclusion of potato flour (T3) with a greater gain in weight, both in the growth stage (402.03 g), as in the fattening stage (644.7 g), with the feeding of the birds in the fattening stages being the most appropriate. To food consumption, it is concluded that the lowest consumption is 3728.97 g to the T3 and the highest is for T0 with the amount of 4069.82 g.